Análisis del estudio del impacto económico de la mano de obra de la empresa Florícola Florycampo S.A. - Parión Pulamarín, Franklin Mauricio (2007)
This research was conducted in a flower production company, Florycampo S.A., an affiliate of the ESMERALDA Group. The company is located in Ecuador, in the County of Cayambe, Ayora Parrish, on the North Panamerican Highway, Km. 2 ½, en route to Otavalo. The main objective of this work was to seek to optimize the time and methods that a qualified worker should spend in a given activity or task, thereby producing a positive effect on the company´s economy. The research was carried out in rose cultivation during harvest, pruning and trimming tasks in the season leading up to Valentine´s Day. Rose cultivation is managed in two systems: hydroponics and in-soil. This research established the differences between these two systems based on labor methods.